(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Irinotecan (CPT-11) is a camptothec in derivative with low oral bioavailability due to active efflux by intestinal P-glycoprotein receptors. Hence, no potent oral formulation is marketed for irinotecan till date and its oral ingestion continues to remain a challenge. This study investigates the potential of supersaturated self-nanoemulsifying drug delivery systems (S-SNEDDS) to improve the bioavailability of poorly water-soluble drugs compared to conventional SNEDDS. Developed formulation comprising of canola oil – caproic acid – propylene glycol revealed particle size of 128.23 nm with PDI 0.137, zeta potential value of -23.45 mV and drug content of 99.32% with spherical shape and smooth surface. A maximum drug release of 99.96% in 60 minutes was observed for formulation F12 hence chosen for screening precipitation inhibitor (PI).The F12 containing 2% HPMC as PI was found to show high release profile. The Fourier transform infrared (FTIR) and Scanning electron microscopy (SEM) studies did not indicate any drug excipient interaction and confirm nanosized particles that are stable. Furthermore, pharmacokinetic studies demonstrated marked improvement of 2.78 fold in wistar rat’s plasma as well as higher oral bioavailability through SNEDDS when compared to pure drug. Hence this approach may be effectively utilized, to replace pre-existing intravenous therapy with enhanced oral bioavailability.